ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING PADA PENAWARAN UMUM PERDANA (STUDI KASUS PADA PERUSAHAAN KEUANGAN YANG GO PUBLIK DI BURSA EFEK JAKARTA TAHUN 2000-2006) - Sri Retno Handayani; Intan Shaferi (Faculty of Economics and Business Universitas Jenderal Soedirman, 2011)
Initial Public Offering (IPO) is activity company in order to public offer of primary share sale. These shares enthused investor because can give initial return. This return indication the happening of share underpricing at primary market when coming on secondary market. Underpricing is conditions which show that stocks price at primary market was to low than secondary market. Intention of this research is to analyse influence variabel-variabel which have an impact to underpricing at financial sector in Jakarta stock exchange during 2000-2006. the factor were Debt to Equity Rasio, Return On Assets, Earning per Share, Company Age, Company Size, Procentaqe of Public offering.There were 28 issuer in financial sector used in study. Analysis was done by using multiple regression. The objective of this research to test the impact of variabel such as Debt to Equity Rato, Return On Assets, Earning per Share, Company Age, Company Size, Percentage of Public offering to underpricing. Result of parsial regression analysis for financial sector indicate that only Earning per Share having a significant effect to underpricing. While by simultan obtained result of Debt to Equity Rasio ,Return On Assets, Earning per Share, Company Age, Company Size, Prosentase of Public offering.that variabel of have no significant effect to underpricing.